Hotel and accommodation booking management platform for travel in Ukraine - Kochura, Vitaly; Loktikova, Tamara; Kushnir, Nadia (Modeling, Control and Information Technologies: Proceedings of International scientific and practical conference, 2025)
A platform for hotel and accommodation booking management is proposed. The platform is built on a monolithic architecture using MVC and Client-Server patterns. The server side is implemented in the PHP programming language using the Symfony framework, and the client side is implemented using the React JavaScript library. The platform uses MySQL as the primary database, supplemented by MongoDB. The developed platform meets modern requirements and has the following features: modern and adaptive design, user-friendly interface with the ability to create a personal account, support for logging in via Google